Designing An Esp Course For Finance And Banking: The Case Of 1st Year Master Students At Abou Bekr Belkaid University, Tlemcen - Slimane MEGHAGHI & Abdelkader BENSAFA (Akofena)
Abstract: This research aims to design an English for Specific Purposes (ESP) course tailored to the needs of first-year Master’s students specializing in Finance and Banking at Abou Bekr Belkaid University, Tlemcen. Given the increasingly globalized nature of finance, proficiency in English is essential for students in this field to access international research, understand global financial practices, and communicate effectively in professional contexts. The study utilizes a needs analysis methodology, involving surveys, interviews, and diagnostic tests to assess the linguistic and professional requirements of these students. Data analysis reveals specific language competencies and skills—such as technical vocabulary, reading comprehension of financial documents, and oral communication skills—that are essential for success in finance and banking. Based on these findings, a course syllabus is proposed, including module structures, language functions, and assessment methods aligned with the students' academic and career needs. This ESP course is designed to not only enhance students' language proficiency but also to equip them with practical skills that directly relate to their future professional environment in finance. The study concludes with recommendations for implementing and evaluating ESP courses in similar contexts. Keywords: ESP; Finance and Banking; needs analysis; syllabus design; language proficiency; Master’s students;University of Tlemcen